Geophysical evidence of first stages of inflation in Domuyo volcanic center in northwestern Neuquén province, Argentina - Godoy, Laura Beatriz (2021)
Cerro Domuyo, in northwestern Neuquén province of Argentina, shows notable geothermal activity, although it is located at a considerable distance from the actual volcanic arc. Many studies have been developed in this area with the aim of investigating its geothermal field. Despite these efforts, the characterization of the dynamic activity in the area is still poorly known. This work shows the results of a network of seismological stations, which registered volcano-tectonic, long-period and hybrid events. A large number of volcano-tectonic events concentrated mostly in the Cerro Domuyo geothermal area were detected. These events can be divided into two groups, those that occurred at shallow depths below the geothermal area and those at greater depths below the high region of Cerro Domuyo. Shallow events were located around the Manchana Covunco fault and many of them were particularly clustered at its intersection with the Humazo fault. Seismicity in the area shows that these faults are continually active due to fluid movement, as was evidenced by the hydrothermal manifestation of the Humazo in 2003. Moreover, new studies provide evidence that the Cerro Domuyo is experiencing an important inflation caused by a magmatic body. Deep volcano-tectonic events are evidencing this activity. Considering the large distance between the actual volcanic arc and the study region, and the high density of shallow volcano-tectonic events, it is highly likely that this magmatic body is increasing the geothermal activity. Additionally, the aeromagnetic anomaly over Cerro Domuyo is showing a thin magnetic crust of less than 6 km, suggesting a clear link between the geophysical results and the inflation in Cerro Domuyo.